Ethnic brands and self-recognition in higher education indigenous students - Cecilia Navia Antezana; Gabriela Czarny Krischkautzky; Gisela Salinas Sánchez (Arizona State University, 2020)
Experiences of young indigenous people who study in an educational program from the National Pedagogical University of Mexico City are analyzed in this work. It puts into question some effects produced by ethnic branded programs, recognizing the contradictions and discriminations that the carrying subjects of these have, with the objective of contribute to the contemporary debate on the modes of self-recognition of indigenous youth in higher education and to stress deeply rooted conceptions such as ethnic identity, which continues to orient education policies in our context. From a qualitative and interpretative perspective, using the technique of focal group, were recognized areas such as linkages and trust with teachers, and how it contributes to the repositioning of subjects, their identity processes and Emancipatory roads. At the same time, it recognizes the present discriminations in the university, which are reinforced in some cases by the essentialist ways of understanding the indigenous presence, and some effects are discussed that produce the affirmative actions, which reflects confronting and contradictory situations in the processes of inhabiting the university from the indigenous student's side.